Qiṣṣat ḥayāt al-Bukhārī: Sīra tārīkhiyya jadīda: (by Aḥmad al-Aqṭash) (American Journal of Islam and Society, 2025)
Few works in Islamic intellectual history have received as much attention as Ṣaḥīḥ al-Bukhārī. With hundreds of premodern and modern studies dedicated to its name, one might assume that little room remains for groundbreaking insights. Khaldūn al-Aḥdab’s recently revised study and the introduction to the Bayt al-Sunna edition of Ṣaḥīḥ al-Bukhārī have made significant contributions to our understanding of Imam al-Bukhārī’s life and works. Yet, Aḥmad al-Aqṭash’s highly anticipated monograph manages to push the boundaries of an extensively studied subject even further. If al-Aqṭash’s gloss on Abū Masʿūd al-Dimashqī’s Jawāb is any indication, he possesses an exceptional mastery of the hadith sciences and is thus well-equipped to engage with the subject at hand.